Diabetes and new-onset atrial fibrillation in a hypertensive population. (2nd April 2016) - Alves-Cabratosa, Lia; García-Gil, Maria; Comas-Cufí, Marc; Martí, Ruth; Ponjoan, Anna; Parramon, Dídac; Blanch, Jordi; Ramos, Rafel
Abstract: Aim The association of diabetes with new-onset atrial fibrillation (AF) remains controversial. Hypertension may partly explain the risk association ascribed to diabetes. We studied the role and characteristics of diabetes in hypertensive patients with no ischemic vascular disease. Methods Records of 262, 892 persons from the Information System for the Development of Research in Primary Care in Catalonia (Spain) were examined from July 2006 to December 2011. Included participants were ≥55-years-old and hypertensive with no ischemic heart disease, stroke, or peripheral artery disease. We used Cox proportional hazards regression to model incidences in the diabetic and non-diabetic subgroups of our population, and among diabetic patients, diabetes duration and pharmacological treatment, hemoglobin A1C, and body mass index. Results New-onset AF incidence in diabetic patients was 13.3 per 1000 person-years (mean follow-up: 4.3 years). In non-diabetic patients, it was 10.4 per 1000 person-years (mean follow-up: 4.1 years). Diabetes hazard ratio (HR) for new-onset AF was 1.11 (95% confidence interval (CI): 1.06–1.16). Diabetic patients also diagnosed with obesity had an HR of 1.41 (95% CI: 1.22–1.64). Conclusion Diabetes was modestly associated with new-onset AF in hypertensive patients with no ischemic vascular disease. Among diabetic patients, only obesity reached significance in its association with this arrhythmia. Key Messages: Diabetes modestly associated with new-onset atrial fibrillation in hypertensive patients with no ischemic vascular disease. In the subgroup of patients with diabetes, only obesity reached significance in its association with atrial fibrillation.